Espiritualidade e empatia: um estudo sobre aspectos espirituais e a relação terapêutica em cuidados paliativos - Liberato, Regina Paschoalucci (2019)
Spirituality as an essential component of human beings is becoming more and more relevant in the context of health care, particularly in palliative care. The objective of this work was to identify the expression of spiritual aspects in the empathic process of the therapeutic relationship between health professionals and the care unit (patient and family) in the palliative care system. A mixed study was conducted using as methodological reference the exploratory and descriptive research. Data collection was carried out by sending a PDF fillable form to healthcare professionals. The questionnaire was composed of two parts. The first one was formatted in the multiple-choice model for the collection of sociodemographic data. The second contained open-ended questions about participants' spirituality, religion, and personal beliefs. The Collective Subject Discourse (DSC) method was chosen for data organization and analysis. Results pointed to the interaction between spirituality, empathic resonance in the exercise of caring, and the concomitant existence of human virtues in palliative care; the perception of spirituality associated with the belief in the connection with a transcendent something or someone, through religiosity or the relation with nature and people, that offers support and meaning to the questions of life and guides ethical conduct; the vision of spirituality as an experience related to concepts such as faith and hope and to the connection of the human with the sacred and the divine, thus showing the multidimensional character of the construct. Other results included the spiritual diversity in the expression of the participants acting as a protective factor for acceptance, support and referral of spiritual problems; the role of self-knowledge related to the improvement in the perception of the other, functioning as a facilitator in the therapeutic relationship; the transpersonal dimension of care coupled with otherness, promoting a rich and creative mutual interaction, through the empathic resonance existing in the exercise of caring; and the notion that the empathic process in the therapeutic relationship in palliative care involves various human capacities and abilities, such as the association of personality resources with talents, values, virtues, and relational and spiritual qualities